2019
DOI: 10.1093/ntr/ntz200
|View full text |Cite
|
Sign up to set email alerts
|

Human Biomarker Exposure From Cigarettes Versus Novel Heat-Not-Burn Devices: A Systematic Review and Meta-Analysis

Abstract: Introduction Novel tobacco products require independent research to assess their safety. This study assessed the current literature for trials comparing levels of biomarkers of exposure (BoE) between conventional cigarettes (CC) and heat-not-burn (HNB) devices. Methods Ten databases were searched using terms including: “heat not burn,” “iqos,” “teeps,” “mrtp,” “tobacco heating,” and “glo” between January 1, 2010 and August 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…These findings are in agreement with the conclusions of two published systematic reviews on the levels of biomarkers of exposure associated with use of heated tobacco products (Drovandi et al, 2020;Akiyama and Sherwood, 2021). The first systematic review identified ten randomised controlled trials involving 1,766 participants published between January 2010 and August 2019 which quantified twelve biomarkers of exposure after controlled use of both heated tobacco products and conventional cigarettes (Drovandi et al, 2020). Seven of these ten studies are detailed in Table 3 whilst the other three articles related to either use of a hybrid product (n=2) or a carbon-heated tobacco product (n=1) both of which are outside the remit of this review.…”
Section: Forced Switching Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with the conclusions of two published systematic reviews on the levels of biomarkers of exposure associated with use of heated tobacco products (Drovandi et al, 2020;Akiyama and Sherwood, 2021). The first systematic review identified ten randomised controlled trials involving 1,766 participants published between January 2010 and August 2019 which quantified twelve biomarkers of exposure after controlled use of both heated tobacco products and conventional cigarettes (Drovandi et al, 2020). Seven of these ten studies are detailed in Table 3 whilst the other three articles related to either use of a hybrid product (n=2) or a carbon-heated tobacco product (n=1) both of which are outside the remit of this review.…”
Section: Forced Switching Studiessupporting
confidence: 92%
“…The authors of this systematic review concluded that "in comparison to conventional cigarettes, all twelve biomarkers of exposure assessed were significantly lower for participants assigned to a heat-notburn device. In comparison to smoking abstinence, heat-not-burn devices were statistically equivalent for eight biomarkers of exposure and significantly elevated for four biomarkers of exposure" (Drovandi et al, 2020). The second systematic review identified twenty-five randomised controlled trials published up to April 2020 which quantified twelve biomarkers of exposure after controlled use of both heated tobacco products and conventional cigarettes (Akiyama and Sherwood, 2021).…”
Section: Forced Switching Studiesmentioning
confidence: 99%
“…4 5 However, current evidence on the harmful effects of HTPs compared with conventional cigarettes is yet to be determined as most of the available evidence is in vitro and comes from tobacco industry-funded research. [6][7][8][9] In July 2020, the Food and Drug Administration (FDA) authorised Philip Morris to make claims in its HTP (IQOS) marketing about reduced exposure to harmful constituents compared with cigarettes; however, the FDA prohibited marketing claims about reduced risks from IQOS use, citing the lack of evidence for this claim. 10 11 Nevertheless, consumers equate reduced exposure with reduced risk 12 : HTPs appeal to adult smokers and use of HTPs has been rapidly increasing in some high-income countries (HIC) where they have been introduced, suggesting a potential public health benefit, similar to that of e-cigarettes.…”
mentioning
confidence: 99%
“…Methods for Quantification of Aerosol Components. The target component levels of TPM captured in the CFP and the centrifuged liquids were determined according to the following procedure: (1) The mass of the total amount of THP aerosols collected on the CFP and the mass change of the CFP before and after centrifugation were measured gravimetrically. (2) For nicotine, glycerol, propylene glycol, and water determination, CFPs were extracted using isopropanol, and the extract was analyzed via gas chromatography with a flame ionization detector (gas chromatography-flame-ionization detection (GC-FID) and gas chromatography with a thermal conductivity detector (GC-TCD) for water), according to the CORESTA recommended method number 84.…”
Section: Schematic Diagram Of a Customized Centrifuge Tubementioning
confidence: 99%
“…Over the past few years, the use of tobacco heating products (THPs) has grown rapidly in many countries around the world. These products have become an attractive alternative to conventional cigarettes because they are considered less risky and are promoted as smoking cessation aids, despite little evidence that they can effectively help smokers to quit. However, there are ongoing concerns about the safety and long-term toxicity of using these products. For example, hazardous chemicals such as toxic carbonyl compounds (acetaldehyde, formaldehyde, and acrolein) have been detected in THP aerosol emissions, while other toxic substances such as heavy metals from heating coils have also been measured.…”
Section: Introductionmentioning
confidence: 99%